Unreal Engine 5 : create a zombie survivor FPS game. (Packt Publishing, 2022)
Unreal Engine, the world's most open and advanced real-time 3D creation system, provides the tools and assets you need to create truly expansive worlds for your players, participants, and stakeholders to explore, using content that scales. Unreal Engine 5 empowers creators across all industries to deliver stunning real-time content and experiences. In this course, you will learn how to make a Zombie Survivor FPS game. You will learn to set up, step-by-step, our first person character, weapons, animations, effects, and more from scratch. We will move on to creating the Zombies AI and the gameplay mechanics. We will also develop Zombie AI that will chase us around and cause damage to our player, use the Matrix Demo scene as environment, or use any environment we wish to build on, from the Unreal Engine Marketplace. The course provides us with all the necessary assets for completing and building the game. By the end of the course, you will learn to create game modes with a complete game scenario and have the knowledge required to create a fantastic FPS Zombie Survivor game using Unreal Engine 5. what You Will Learn Learn to program using Blueprints without needing to write codes Set up an FPS human-controlled character from the beginning Connect and animate FPS and weapons using custom animations Create movement and game logic using the Blueprints system Create a zombie artificial intelligence system Build a complete FPS zombie game on the Unreal Engine 5 environment Audience This course is ideally for those who want to make their video games using Unreal Engine. This course is for those individuals who wish to develop games but do not want to or know how to write lengthy gaming codes. Developers with experience in other engines, such as Unity, or artists who want to create their projects and games will benefit from this course. A PC or Mac capable of running Unreal Engine 5, about 15GB of free disc space, and at least 8GB of RAM along with basic Unreal Engine 5 skills is required. This course does not cover the basics of Unreal Engine 5. About The Author Ivan Yosifov: Ivan Yosifov is a 3D Artist and co-founder at Seven Bulls Games Ltd. He creates online courses in 3D/2D and game art. He owns a studio that is focused on developing AAA mobile shooter games. He has more than 12 years of experience in the mobile game development industry. He has a bachelor's degree in computer technology. He is also the winner of the Sofie Game Jam 2016.